Sugammadex associated profound bradycardia and sustained hypotension in patient with the slow recovery of neuromuscular blockade - A case report - Choi, Yong Jun; Park, Jeong Wook; Kim, Sang Hun; Jung, Ki Tae (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: New complications associated with sugammadex have been increased since its widespread use. We report a case of an 80-year-old male who experienced profound bradycardia and sustained hypotension after administration of sugammadex. Case: Following administration of 200 mg sugammadex after laparoscopic cholecystectomy, sudden bradycardia (29 beats/min) developed for 10 seconds and his trainof- four (TOF) ratio remained at 0.2 for 5 min. An additional 200 mg sugammadex was administered and profound bradycardia (21–30 beats/min) and hypotension (60/40 mmHg) developed. Atropine at 0.5 mg was administered, but the effect lasted only 30 s. Profound bradycardia occurred four more times at 30 s intervals, and ephedrine and phenylephrine were injected intermittently to increase the patient’s heart rate and blood pressure. The TOF ratio became 0.9 about 10 min after administration of additional sugammadex. Conclusions: Awareness must be heightened regarding the possibility of sugammadexinduced bradycardia and hypotension, and more attention should be paid to patients with slow recovery times following muscle relaxation, despite the use of sugammadex. KCI Citation Count: 0